Exploring the affordances of text and picture stories - Öncel, Püren; Hu, Shu; Ness-Maddox, Heather; Allen, Laura K.; Magliano, Joseph P. (Discourse processes, 2024)
We often talk about our narrative experiences with others. For example, we might talk about the latest TV show or book in a series with friends. How does the media of a narrative (text, picture story) affect how we talk about it? Despite the fact that narratives can be experienced across different media, few studies have addressed the impacts of varied media. This study explored similarities and differences in how narratives are experienced across text and sequential picture stories. Picture and text versions were used for the same stories. Participants (n = 132) engaged in a think-aloud task at specific story units and provided ongoing think-aloud responses while reading or viewing. Natural language processing analyses were then conducted on the think-aloud responses. Results indicated that participants produced more words reflecting the internal states of characters and causality when reading than when viewing picture stories. Conversely, they produced more place words when viewing picture stories than reading text. Implications for theory and future directions are discussed.